Compressive Creep Behavior of High-Pressure Die-Cast Aluminum-Containing Magnesium Alloys Developed for Elevated Temperature Applications - Gavras, Sarkis; Zhu, Suming; Easton, Mark A.; Gibson, Mark A.; Dieringa, Hajo (Frontiers in Materials, 2019)
In addition to AZ- and AM-series magnesium alloys, which are mainly used at ambient temperature, there are also die-cast magnesium alloys developed for use at elevated temperatures. This paper examines the compressive creep resistance of several aluminium-containing magnesium high-pressure die-cast alloys, including the commercially available AE42, AE44-2, AE44-4, MRI230D alloys and newly developed DieMag series, i.e. DieMag211, DieMag422 and DieMag633. Compressive creep is the common load case for automotive powertrain components such as transmission housings, engine blocks or oil pans, which are typically mounted with steel or aluminium bolts that have lower thermal expansion than magnesium alloys. When the components heat up, there is a compressive load in the area around the bolt. The compressive creep experiments are accompanied by microstructure investigations. It is shown that MRI230D and the two high-concentrated DieMag alloys have the best creep resistance at 200°C. Similar results are also observed in the tensile tests at room temperature and 150°C, with DieMag633 showing outstanding strength.